The precise function of alphaherpesvirus tegument proteins and their interactions during the viral life cycle - Cui, Yuxi; Wang, Mingshu; Cheng, Anchun; Zhang, Wei; Yang, Qiao; Tian, Bin; Ou, Xumin; Huang, Juan; Wu, Ying; Zhang, Shaqiu; Sun, Di; He, Yu; et al. (Frontiers in Microbiology, 2024)
Mingshu Wang contributed equally to this work.Alphaherpesvirus is a widespread pathogen that causes diverse diseases in humans and animals and can severely damage host health. Alphaherpesvirus particles comprise a DNA core, capsid, tegument and envelope; the tegument is located between the nuclear capsid and envelope. According to biochemical and proteomic analyses of alphaherpesvirus particles, the tegument contains at least 24 viral proteins and plays an important role in the alphaherpesvirus life cycle. This article reviews the important role of tegument proteins and their interactions during the viral life cycle to provide a reference and inspiration for understanding alphaherpesvirus infection pathogenesis and identifying new antiviral strategies.